PENGARUH SERVICE EXCELLENCE, CUSTOMER EXPERIENCE DAN BRAND TRUST TERHADAP CUSTOMER LOYALTY (Studi Kasus Pengguna Jasa Grab di Kota Bengkulu) - Ratnawili Ratnawili; Marliza Ade Fitri; Eti Arini (Universitas Muhammadiyah Bengkulu, 2021)
ABSTRACTThis study aimed to determine the effect of Service Excellence, customers’ experience and Brand Trust toward customers’ loyalty to Grab service users Bengkulu city. This study used a sample of 95 online grab motorcycle taxi consumers in Bengkulu city. The data collection techniques used a questionnaire. The analysis technique of this study used multiple linear regression, coefficient of determination and hypothesis testing. The results of multiple regression research show a positive direction, namely Y = 0.261 + 0.209 X1 + 0.335X2 + 0.261 X3. The determination coefficient test of the adjusted R square is 0.476. This means that X1 (Service Excellence), X2 (customers’ experience) and X3 (Brand Trust) have a contribution to customers’ loyalty (Y) by 47.6% while the remaining 52.4% is influenced by other factors that are not examined in this research. The results of the hypothesis test partially show that Service Excellence has a positive and significant effect toward customers’ loyalty to Grab service users in Bengkulu city. Customers’ experience has a positive and significant impact on customers’loyalty to Grab service users in Bengkulu city. Brand Trust has a positive and significant effect toward customers’ loyalty to Grab service users in Bengkulu city. Simultaneous hypothesis test results show that Service Excellence, customerS’ experience and Brand Trust have a positive and significant effect toward customers’ loyalty to Grab service users in Bengkulu city.Keywords: Satisfaction, Trust, and Purchase Intention